Basic First Aid and Physical Health Training for the Tourism Community of Karian Reservoir in Priority Development Areas, Lebak Regency, Banten - Dedi Aryadi; Ira Arini; Eka Setiawati (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2026)
This community service program is a grant initiative from the Ministry of Higher Education of the Republic of Indonesia under the 2025 Student Executive Board (BEM) Community Empowerment Scheme. Karian Dam has become an increasingly popular tourist destination, which raises the potential risk of accidents due to water-based and outdoor activities. However, the local community’s ability to provide first aid and maintain physical fitness is still limited, and safety facilities at the tourist site remain inadequate. This program provides basic first aid and physical health training to residents living around the Karian Dam area to improve emergency preparedness. The training materials include basic CPR skills, minor wound treatment, and fitness education to promote a healthy lifestyle. The implementation methods include lectures, demonstrations, simulations, and guided practice. The program also introduces innovations such as a community first aid kit and interactive infographic posters based on Augmented Reality (AR). Evaluation results show a significant improvement in participants’ knowledge and skills, with an average score increase of +16 points. Participants responded positively to the technological innovations introduced and are expected to strengthen emergency preparedness and contribute to a safer, healthier, and more sustainable tourism environment at Karian Dam.